answer is equal to 2X44/5mile=17.6mile
Each section of a race is 25 mile.
The race has 4 sections.
Which expression tells how many miles long the entire race is?
Answer:
4×2/5
A scientist use 2 gallons of liquid for every 3 hours he works he uses blank of a gallon each hour he works
What is the solution to the system of equations?
-3 x - 4y - 3z= -7
, 2x - 6 y + 2z= 3,
5 x - 2y + 5 Z=9
Answers:
A, (5, -2, 7)
B, (-5, 2, 7,)
C, (5,2,-7)
D, No solution
Solution
Step 1: Isolate the variable x and plug in the values of x in the second and third equations.
Step 2: Isolate variable y and solve for y.
We get the value of y = 5/26
When we substitute the value of y , 1 = 0 which is not true.
Therefore, this system has No Solution.
Answer: No solution
Marta drew a scale drawing of her backyard. She used the scale 1/2 inch =4.5 feetif the actual length of her backyard is 54,what is her scale drawing in inches
1/2 inch…………4.5 feet
x inches……….54 feet
x=(54•1/2)/4.5
x=27/4.5
x=6 inches
A bookstore buys algebra 1 books at a wholesale price of $17 each. It then marks up the price by 55%, and sells the algebra 1 books. What is the amount of the markup? What is the selling price?
The amount of markup is $9.35 .The selling price of algebra1 books after 55% increment is $26.35
What is the method to calculate x% increment?If there is x% increment in y then the increment will be (x/100)*y and the new amount after x% increment will be now y + (x*y)/100
A bookstore buys algebra 1 books at a wholesale price of $17 each.
Initial price of algebra 1 book was = $17
There is 55% increment in books price before selling
55% of initial price = (55/100)*17 = 935/100= $9.35
The selling price = wholesale price + 50% increment = 17 + 9.35 =26.35
Therefore, the amount of markup or increment is $9.35 the selling price of the algebra 1 books after 55% markup is $ 26.35.
Also, Learn more about the percentage increment from the link below:
brainly.com/question/27758670
#SPJ2
What are the discontinuities of the function f(x) = the quantity x squared minus 36 over the quantity 4x plus 24?
there is a point discontinuity ( hole ) at (- 6, - 3 )
factor the numerator/denominator
f(x) = [tex]\frac{(x-6)(x+6)}{4(x+6)}[/tex]
the factor (x + 6) cancels leaving the simplified version of f(x)
f(x) = [tex]\frac{x-6}{4}[/tex]
the removal of the factor (x + 6) from the numerator/denominator means there is a discontinuity at x + 6 = 0 , that is x = - 6
f(- 6 ) = [tex]\frac{-6-6}{4}[/tex] = - 3
there is a point discontinuity ( hole ) at (- 6, - 3 )
Patients who are addicted to cocaine are sometimes using the drug to combat depression. As such, sometimes addicts are given antidepressant medications to prevent relapse. A three-year study compared the effects of two such medications, lithium and desipramine, along with a placebo for 72 cocaine users wishing to break the habit. The patients were put into 3 groups of 24, and given 1 of the 3 treatments at random. This two-way table illustrates the results.
Treatment Relapse No relapse Total
Desipramine 10 14 24
Lithium 18 6 24
Placebo 20 4 24
Total 48 24 72
Give a conditional relative frequency for relapse among patients who took lithium.
A. 18/72 = 25%
B. 27/72 = 33.33%
C. 18/24 = 75%
D. 48/72 = 66.67%
Answer:
Option C, 18/24 = 75%
Step-by-step explanation:
Patients who were addicted to cocaine were divided into 3 groups of 24.
Each group was treated with three different drugs. One group of 24 patients were put on Lithium for treatment out of 24 patients who relapsed were 18.
So conditional relative frequency for relapse among patients who took Lithium would be :
Relative frequency of patients = (patients relapsed) / (total number of patients)
Relative frequency = [tex]\frac{18}{24}[/tex] = 75%
Option C, 18/24 = 75% would be the answer.
Helppppppppppppppppp
The definitions of the labels are:
acute - less than 90°right - exactly 90°obtuse - more than 90°straight - exactly 180°Since RQU is the sum of RQS, SQT and TQU, it measures 19+71+18 degrees, i.e. 108 degrees, and thus it's obtuse
Similarly, SQU is the sum of SQT and TQU, so it measures 71+18 = 89 degrees, so it's acute.
Finally, RQT is the sum of RQS and SQT, so it measures 19+71=90 degrees, and it's a right angle.
obtuse, acute and right
∠RQU = 19° + 71° +18° = 108° ⇒ obtuse angle
∠SQU = 71° + 18° = 89° ⇒ acute
∠RQT = 19° + 71° = 90° ⇒ right
Lamar is solving the equation x^2 - 12x = -6 by completing the square. Which shows lamar's next step and the solution to the equation?
step 1: x^2 -12x = 6
step 2: x^2 - 12x + 36 = -6 +36
Answer:
[tex]x^2-12x+36= -6+36[/tex]
Step-by-step explanation:
Equation : [tex]x^2-12x = -6[/tex]
General equation : [tex]ax^2+bx+c=0[/tex]
So,we need to add and subtract [tex](\frac{b}{2})^2[/tex] for completing square.
So, next step of completing square :
[tex]x^2-12x+6^2-6^2= -6[/tex]
[tex]x^2-12x+36= -6+36[/tex]
Hence Step 2 shows lamar's next step and the solution to the equation
The solution to the equation after completing the square is:
(x - 6)² = 30
How to find the next stepLamar starts with the equation x² - 12x = -6.
Step 2: To complete the square, Lamar takes the coefficient of the x term, which is -12, divides it by 2, and then squares it. In this case, (-12/2)² = 36.
Lamar adds 36 to both sides of the equation to maintain its balance. By doing so, he effectively creates a perfect square trinomial on the left side of the equation.
x² - 12x + 36 = -6 + 36
Simplifying the right side, -6 + 36 equals 30.
The equation now becomes:
x² - 12x + 36 = 30
Now, Lamar can rewrite the left side of the equation as a perfect square. The left side is (x - 6)² because (x - 6)(x - 6) equals x² - 12x + 36.
(x - 6)² = 30
Thus, the solution to the equation x² - 12x = -6, after completing the square, is (x - 6)² = 30.
Learn more about equation at
https://brainly.com/question/29174899
#SPJ6
Alonzo's gas tank is 1/3 full. After he buys 3 gallons of gas, it is 1/2 full. How many gallons can Alonzo's tank hold?
3. At a bargain store, Tanya bought 3 items that each cost the same amount. Tony bought 4 items that each cost the same amount, but each was $2.25 less than the items that Tanya bought. Both Tanya and Tony paid the same amount of money. What was the individual cost of each person's items?
(a) Write an equation. Let x represent the cost of one of Tanya's items.
(b) Solve the equation. Show your work.
(c) Check your solution. Show your work.
(d) State the solution in complete sentences.
By setting up an equation with x as the cost of Tanya's items, we find that each of Tanya's items cost $9.00. Tony's items, being $2.25 cheaper, cost $6.75 each. The solution is checked by ensuring both Tanya's and Tony's total expenditure was equal.
The question asks us to find the individual cost of items purchased by Tanya and Tony at a store, given that Tony's items each cost $2.25 less than Tanya's but both spent the same amount overall.
Equation Setup
Let x represent the cost of one of Tanya's items. Since Tanya bought 3 items, she spent 3x dollars. Tony's items each cost $2.25 less, so they cost (x - $2.25) each. Tony bought 4 items, spending 4(x - $2.25). Since both spent the same amount:
3x = 4(x - $2.25)
Solving the Equation
To solve for x:
Distribute the 4 on the right side of the equation to get 3x = 4x - $9.00.Subtract 4x from both sides to get -x = -$9.00.Divide both sides by -1 to get x = $9.00.So, each of Tanya's items cost $9.00.
Checking the Solution
To verify:
Tanya's total is 3($9.00) = $27.00.Tony's total is 4($9.00 - $2.25) = 4($6.75) = $27.00.Both totals match, confirming that the solution is correct.
Tanya's items each cost $9.00, while Tony's items, costing $2.25 less, each cost $6.75.
$1,200 is invested in an account earning 6.5% interest compounded annually. How much will there be in the account after 3 years?
Answer:
B. $1,449.54
Step-by-step explanation:
That's the answer
Find 0.45 of 80 A.36 B.3.6 C.0.36 D.0.036
A
the word 'of' means to multiply
0.45 × 80 = 36
How would i number the graph
Allen score in the video game was changed by -75 points because he miss some targets he got -15 points for each miss target how many targets did he miss
Answer:
he missed 5 targets
Step-by-step explanation:
The average height of a female giraffe is4.6 meters What is her height in centimeters
460 cm
note that 1m = 100 cm, thus
4.6m = 4.6 × 100 = 460 cm
Simplify the expression given below.
x-3/x-1 + 6/x-3
Answer:
Step-by-step explanation:
x2+3/x2-4x+3
Answer:
x^2+3/(x-1)(x-3)
Step-by-step explanation:
A lecture hall seats 220 people. If 99 people are in the lecture hall, what percentage of the seats are filled?
Answer:
45%
Step-by-step explanation:
To find the percent, we write the information as part/whole:
99/220
Now we convert to a decimal by dividing:
99/220 = 99÷220 = 0.45
Lastly, multiply by 100:
0.45(100) = 45
A babysitter earns 8.50$ for 1 hour and 34$ for 4 hours if she works 18.5 hours one weekend what was her earning for the weekend
A pump can supply 5 units of water per minute. How many minutes will it take to fill a 800 unit tank to its full capacity if it is already 1/4 full of water?
It will take 120 minutes to fill up
The pump will take 120 minutes to fill the tank.
To answer the question of how many minutes it will take to fill an 800-unit tank that is already 1/4 full using a pump that can supply 5 units of water per minute, we must first determine the amount of water needed to fill the tank completely.
Since the tank is 1/4 full, it already contains 800 units * 1/4 = 200 units of water. Therefore, the remaining volume to fill is 800 units - 200 units = 600 units. Next, we divide this remaining volume by the rate at which the pump supplies water:
600 units / (5 units/minute) = 120 minutes.
It will take 120 minutes to fill the tank to its full capacity.
Geometry help , only answer if your sure please. The question is in the attached
J(1 , 0); N(5, 0) ; M(5 , -3) and P(2 , -5)
Translation (x,y) -->(x-4, y+4)
J'(-3,4), N'(1, 4) ; M'(1 , 1) and F'(-2 , -1)
Answer is C)
J'(-3,4), N'(1, 4) ; M'(1 , 1) and P'(-2 , -1)
Please help asap 25 pts
[tex]7x > -35\qquad|\text{divide both sides by 7}\\\\x > -5\\------------------------------------\\\\3x\leq30\qquad|\text{divide both sides by 3}\\\\x\leq10\\\\Answer:\ b)\ -5 < x\leq10[/tex]
Principal: $750,00; annual interest rate: 5 percent. What is the interest after 6 months?
Final answer:
To calculate the interest after 6 months with a principal of $750,000 and an annual interest rate of 5%, you need to convert the annual rate to a monthly rate and then use the formula Interest = Principal × Rate × Time. The interest after 6 months is $1,562.50.
Explanation:
To calculate the interest after 6 months, we can use the formula:
Interest = Principal × Rate × Time
Here, the principal is $750,000, the annual interest rate is 5%, and the time is 6 months.
First, we need to convert the annual interest rate to a monthly rate:
Monthly interest rate = Annual interest rate / 12
Monthly interest rate = 5% / 12 = 0.4167%
Now, we can calculate the interest:
Interest = $750,000 × 0.4167% × 6/12
Interest = $1,562.50
A system of equations is given below:
(x+1)^2 + (y-4)^2 = 9
y=x+2
Which choice represents a solution to this system of equations?
A. (-2,0)
B. (1,-1)
C. (2,4)
D. (-1,4)
[tex]A.\ (-2,\ 0)\\\\substitute\ to\ y=x+2\\\\0=-2+2\\0=0\ CORRECT\\\\substitute \ to\ (x+1)^2+(y-4)^2=9\\\\(-2+1)^2+(0-4)^2=9\\(-1)^2+(-4)^2=9\\1+16=9\\17=9\ \ FALSE[/tex]
[tex]B.\ (1,\ -1)\\\\substitute\ to\ y=x+2\\\\-1=1+2\\-1=3\ \ \ FALSE[/tex]
[tex]C.\ (2,\ 4)\\\\substitute\ to\ y=x+2\\\\4=2+2\\4=4\ \ \ CORRECT\\\\substitute\ to\ (x+1)^2+(y-4)^2=9\\\\(2+1)^2+(4-4)^2=9\\3^2+0^2=9\\9+0=9\\9=9\ \ \ CORRECT[/tex]
[tex]D.\ (-1,\ 4)\\\\substitute\ to\ y=x+2\\\\4=-1+2\\4=1\ \ \ \ FALSE[/tex]
Answer: C. (2, 4)A plane can fly 11 miles per minute the plane will fly 6 trips and eat shrimp is 500 miles how many hours will the plane fly
If i understand the question correctly the plane will fly 6 trips of 500 miles each trip.
Number of minutes it takes the plane to fly 500 miles
= 500 / 11
= 45.45 minutes
For 6 trips this = 45.45 * 6 = 272.73 minutes
= 4.55 hours to nearest hundredth.
Select the multiplication sentence that applies the associative property of multiplication to the example. Example: 6 × (4 × 2) = 48 A. (6 × 7) + 6 = 48 B. 6 × (4 + 2) = 36 C. (6 + 4) × 2 = 20 D. (6 × 4) × 2 = 48
answer : D
A. (6 × 7) + 6 = 48
Associative property of multiplication . Here we have +6 . there is a + sign inbetween. so it does not comes under Associative property of multiplication
B. 6 × (4 + 2) = 36
Here we have 4 +2 . there is a + sign inbetween. so it does not comes under Associative property of multiplication
C. (6 + 4) × 2 = 20
Here we have 6 + 4 . there is a + sign inbetween. so it does not comes under Associative property of multiplication
D. (6 × 4) × 2 = 48
Here we have 6 times 4 times 2. so it comes under Associative property of multiplication
WILL GIVE BRAINLIEST!!! PLEASE HELP!
write a mathematical equation stating that three consecutive even integers add up four times the smallest
PLEASE HELP!!!!!!!!!!!!!!!
Hey there!!
Let's take the first number an the smallest number as ' x '
Then, the second consecutive even integer would become ' x + 2 '
Third integer ' x + 4 '
Hence, adding them up, we get,
x + x + 2 + x + 4
... 3x + 6
This is equal to 4 times the smallest number.
We got the smallest number as ' x '
Hence, the final equation :
... 3x + 6 = 4x
Hope my answer helps!!
Which equation illustrates the additive inverse property?
A.
6 + 0 = 6
B.
6 + (-6) = 0
C.
6 × 0 = 0
D.
-6 + 6 = 6 + (-6)
Final answer:
The equation that demonstrates the additive inverse property is B. 6 + (-6) = 0, where 6 and -6 are additive inverses of each other.
Explanation:
The equation that illustrates the additive inverse property is B. 6 + (-6) = 0. The additive inverse property states that for any number 'a', there is a number '-a' such that 'a' plus '-a' equals zero. This is because adding a number to its additive inverse (which is the negative of the number) will result in zero.
Examples demonstrating the additive inverse include subtracting a positive number and changing its sign before operating the addition, for instance, 5-(+3) results in 5-3, which equals 2. Conversely, if you subtract a negative number, like subtracting -6 from 2, you would perform 2-(-6) which equals 2+6, resulting in 8.
Running out of time! Please help and show work! Thank you! Will mark brainliest!
(-3j²k³)²(2j²k)³ = When a power is raised to a power the exponents have to be multiplied.
= (-3²j⁽²*²⁾k⁽³*²⁾)(2³j⁽²*³⁾k³) = We can take out the constants
= (9)(8)(j⁴k⁶)(j⁶k³) = We can group the same variables
= 72(j⁴j⁶)(k⁶k³) = When multiplying two powers that have the same base, you have to add the exponents.
= 72 j⁽⁴⁺⁶⁾k⁽⁶⁺³⁾ = 72j¹⁰k⁹
Answer = 72j¹⁰k⁹
Hope this helps!
[tex]\textit{\textbf{Spymore}}[/tex]
Which best describes the association between variables x and y?
A. Strong Positive
B. Strong Negative
C. Weak Positive
D. Weak Negative
Answer: C. Weak Positive
Step-by-step explanation:
In a scatter plot , a positive correlation is a relationship between the two variables x and y in which if value at x axis increases, then other value at y axis also increases.
In the given scatter plot the the association between variables x and y is a weak positive correlation because there is a lower likelihood in the relationship between variables.
Write the equation of the line through the given point. Use slope-intercept form. (−9,7) perpendicular to y=-5/6x+6
GIVEN: y = -5/6x + 6
slope of given line = -5/6
--> Because the line you are trying to find is perpendicular to the given line, you must find the opposite reciprocal of the slope
opposite reciprocal of the slope = 6/5
You need to find what "b" is for your equation
y = mx + by = 6/5x + b7 = (6/5)(-9) + b7 = -54/5 + b89/5 = b17.8 = bPlug "b" back into the slope-intercept form along with your equation's slope
y = mx + b
ANSWER: y = 6/5x + 17.8(if your teacher doesn't want any decimals, then write: y = 6/5x + 89/5)
The equation of the line that is perpendicular to y=-5/6x+6 and cross through the point (-9,7) is y = 6/5x + 29.8, found by using the slope-intercept form and the concept of negative reciprocal slopes.
Explanation:To find the equation of the line that is perpendicular to y=-5/6x+6 and crossing through the point (-9,7), we first need to find the slope of that line. We can determine that by knowing that the slopes of perpendicular lines are negative reciprocals of each other. So, if the slope of given line is -5/6, the slope of the line perpendicular to it will be the negative reciprocal, which is 6/5.
Now we have a point (-9,7) and a slope (6/5) and can use the slope-intercept form of a line to write the equation of a line.
We use the formula y = mx + b:
Where 'y' and 'x' are coordinates of a point on the line, 'm' is the slope, and 'b' is the y-intercept. We know 'm', 'y' and 'x', so we can solve for 'b'. Substituting, we get: 7 = (6/5)(-9) + b, which simplifies to b = 29.8.
The equation of the line in slope-intercept form is: y = 6/5x + 29.8
Learn more about Line Equations here:https://brainly.com/question/35689521
#SPJ2